A Hydro-mechanical Model and Analytical Solutions for Geomechanical Modeling of Carbon Dioxide Geological Sequestration - Zhijie Xu; Yilin Fang; Timothy. D. Scheibe; Alain Bonneville (The Minerals, Metals and Materials Society, 2012)
"We present a hydro-mechanical model for geological sequestration of carbon dioxide. The model considers the poroelastic effects by taking into account the coupling between the geomechanical response and the fluid flow in greater detail. The simplified hydro-mechanical model includes the geomechanical part that relies on the linear elasticity, while the fluid flow is based on the Darcy's law. Two parts were coupled using the standard linear poroelasticity. Analytical solutions for pressure field were obtained for a typical geological sequestration scenario. The model predicts the temporal and spatial variation of pressure field and effects of permeability and elastic modulus of formation on the fluid pressure distribution.IntroductionIn order to achieve a substantial reduction of CO2 emissions and alleviate the atmospheric carbon problem, massive scale carbon sequestration is required involving millions of tons of carbon dioxide injection over several decades. The geomechanical response is important upon the injection of substantial supercritical carbon dioxide into deep geological formations. Supercritical CO2 is less dense than brine waters and the buoyancy driven flow of CO2 requires the aquifer to be capped by low permeability rock (""caprock"") to prevent the upward migration of C02 (as shown in Fig.1 ). Massive scale injection of C02 changes the overall stress state in the caprock and formation. This change leads to large deformation that can damage the caprock, create fractures, and open new flow paths for supercritical C02. Therefore, a coupled hydromechanical model becomes essential for the caprock integrity analysis."